Production of teak seedlings in different organic substrates (Research, Society and Development, 2021)
Teak (Tectona grandis L.f.) is a tree of Asian origin that has been widely planted in Brazil; however, its use is restricted due to the difficulty in producing seedlings, being the use of organic compounds an alternative for its production. Therefore, the objective was to evaluate the use of goat manure, decomposed trunk of babassu palm and bokashi as components of substrates in the production of teak seedlings. The experiment was carried out in a nursery for 60 days. A completely randomized design was used, with ten treatments, substrates composed of goat manure (EC1, EC2 and EC3), decomposed trunk of babassu palm (CB1, CB2 and CB3) and bokashi (BO1, BO2 and BO3), with proportions of 45, 30 and 15%, respectively, associated with the soil, with a control treatment with 100% soil (Latosol Red-Yellow Dystrophic), and four repetitions. The height of the aerial part, the diameter of the stem at the neck level, the number of leaves and the Dickson Quality Index were evaluated. The data were analyzed using the InfoStat © software and the averages compared using the Duncan test. The use of bokashi and goat manure as substrate components for the production of teak seedlings allows favorable yields. The use of at least 15%, bokashi or goat manure allows the formation of better quality seedlings.